2010
DOI: 10.1002/lsm.20857
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy: New treatment for recalcitrant Malassezia folliculitis

Abstract: BackgroundMalassezia folliculitis commonly has been treated with oral antifungal medications. However, it has many therapeutic weaknesses such as infection relapse, drug resistance, or adverse effects like hepatotoxicity and gastrointestinal discomfort. Hence, there remains an ongoing need for alternative treatments for recalcitrant Malassezia folliculitis. Recently, many dermatologists suggest photodynamic therapy (PDT) as an alternative therapeutic option for its antimicrobial effect.ObjectiveTo investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…In another clinical trial of 30 patients with onychomycosis, patients that received aPDT therapy combining ALA and red light (570–670 nm, dose of 40 J/cm 2 ) had a 43% cure rate at 12 months after the treatment and 37% remained disease free at 18 months (Sotiriou et al, 2010). Lee et al (2010) reported that four of six patients with recalcitrant Malassezia folliculitis demonstrated significant improvement after treatment with methyl 5-ALA (MAL)-PDT and red LED light (630 nm, light dose of 37 J/cm 2 ).…”
Section: Pdt For Human Fungal Infectionsmentioning
confidence: 99%
“…In another clinical trial of 30 patients with onychomycosis, patients that received aPDT therapy combining ALA and red light (570–670 nm, dose of 40 J/cm 2 ) had a 43% cure rate at 12 months after the treatment and 37% remained disease free at 18 months (Sotiriou et al, 2010). Lee et al (2010) reported that four of six patients with recalcitrant Malassezia folliculitis demonstrated significant improvement after treatment with methyl 5-ALA (MAL)-PDT and red LED light (630 nm, light dose of 37 J/cm 2 ).…”
Section: Pdt For Human Fungal Infectionsmentioning
confidence: 99%
“…Patients underwent three sessions of MAL-PDT at 2-week intervals. One month after the last PDT treatment, patients returned to the hospital and lesions were photographed (Lee et al, 2010). After three sessions of MAL-PDT, inflammatory lesions had decreased and improved obviously in four patients, had improved slightly in one patient, and had not improved in one patient.…”
Section: Antimicrobial Pdt: From Bench Top To Bed Sidementioning
confidence: 99%
“…Lately, a few articles concerning the use of MNs on human skin were published. However, the first study concerns not as much the use of MNs as about a new condition, Recalcitrant Malassezia Folliculitis (6). The second study, although about the use of MNs in PDT, has a few drawbacks.…”
Section: Introductionmentioning
confidence: 97%
“…Lately, several reports show the positive effect of PDT against bacteria, viruses, fungi and protozoa (3)(4)(5)(6). The major drawbacks of topical PDT are shallow penetration depth (<2 mm) of ALA and MAL and pain experienced during light exposure (2,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%